2021
DOI: 10.1007/s11356-021-12943-5
|View full text |Cite
|
Sign up to set email alerts
|

Detection and removal of microplastics in wastewater: evolution and impact

Abstract: The pervasiveness of microplastics in aquatic ecosystems has become a major environmental issue in recent years. The gradual dumping of plastic wastes, inadequate standard detection methods with specific removal techniques, and slow disposal rate of microplastics make it ubiquitous in the environment. Evidence shows that microplastics act as a potential vector by adsorbing different heavy metals, pathogens, and other chemical additives widely used in different raw plastic production. Microplastics are ingested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(46 citation statements)
references
References 182 publications
(201 reference statements)
0
46
0
Order By: Relevance
“…Microplastics are on the rise as an emerging pollutant in aquatic ecosystems that have affected the environment for many years (Lam et al 2022). Rivers, seas, and oceans have been affected by microplastics environmental pollution and have been a source of environmental concern for decades (Dey et al 2021;Fan et al 2021a). Today, the use of plastics and plastic products is so widespread that the idea of life without them may not be understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microplastics are on the rise as an emerging pollutant in aquatic ecosystems that have affected the environment for many years (Lam et al 2022). Rivers, seas, and oceans have been affected by microplastics environmental pollution and have been a source of environmental concern for decades (Dey et al 2021;Fan et al 2021a). Today, the use of plastics and plastic products is so widespread that the idea of life without them may not be understood.…”
Section: Introductionmentioning
confidence: 99%
“…Global plastic production has increased exponentially since the 1950s, and in recent years has raised global concerns about improper plastic disposal and the widespread distribution of plastic waste in the environment. For example, as packaging or building materials or clothing, and has become an important part of our waste (Dey et al 2021;Naji et al 2019). The production and development of thousands of new plastic products accelerated after World War II and transformed the new era in such a way that life without plastics is now unthinkable for humans (Schröder et al 2021b;Yogalakshmi and Singh 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that algae and brown algae tend to adsorb microplastics due to the presence of alginic acid in their walls. The functional carboxyl group is present in brown algae, and thanks to this group, the plastic can bind to the adsorbent [ 100 , 101 ].…”
Section: Mitigation Measures For Microplastic Contaminationmentioning
confidence: 99%
“…Electrocoagulation is a treatment process in which cations are formed by metal electrodes in an electrical field [68,69]. It produces coagulants using metal electrodes that are more likely to encounter pharmaceutical products with several advantages, including sludge minimization, automatic treatment, and efficient and low operating costs [69,70]. The removal efficiency of the three most consumed pharmaceutical products such as carbamezapine (70%), diclofenac (90%), and amoxicillin (77%) was investigated by Ensano et al [71] for a density of 0.5 mA/cm 2 , an initial concentration of 10 mg/L, and a hydraulic retention time HRT of 38 h. Oxytetracycline, an antibiotic drug, was analyzed by Nariyan et al [72].…”
Section: Electrocoagulation Processmentioning
confidence: 99%